Can the Third Wave Speak? - Henderson, Jennifer (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This article suggests that self-proclaimed third-wave feminism is tied to institutional imperatives and impasses in Women's Studies. It offers an alternative contemporary feminist tendency in "cryptofeminism," which suspends the necessity of affirming feminist identity and reflects critically on the unpredictable uses and legacies of feminist thought.